Viksit Bharat 2047: India’s Journey Towards Inclusive and Sustainable Development - Surekha M., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Viksit Bharat 2047: India’s Journey towards Inclusive and Sustainable Development explores India’s long-term vision to become a developed nation by the centenary of its independence. Moving beyond conventional growth metrics, the Viksit Bharat agenda emphasizes inclusive prosperity, robust governance, environmental sustainability, and human capital development. Anchored in historical context, the vision builds on India’s post-independence planning, economic liberalization, and contemporary flagship initiatives such as Atmanirbhar Bharat, PM Gati Shakti, and Digital India. The study highlights policy strategies and structural reforms aimed at leveraging technology, fostering entrepreneurship, and strengthening global integration. By presenting a multidimensional roadmap, this paper underscores India’s ambition to achieve holistic development, ensuring that growth is equitable, sustainable, and globally competitive by 2047.
Keywords: Viksit Bharat 2047; Inclusive Development; Sustainable Growth